First Genome-Wide Association Study in an Australian Aboriginal Population Provides Insights into Genetic Risk Factors for Body Mass Index and Type 2 Diabetes - Anderson, Denise (PLoS One, 2015)
A body mass index (BMI) >22kg/m(2) is a risk factor for type 2 diabetes (T2D) in Aboriginal Australians. To identify loci associated with BMI and T2D we undertook a genome-wide association study using 1,075,436 quality-controlled single nucleotide polymorphisms (SNPs) genotyped (Illumina 2.5M Duo Beadchip) in 402 individuals in extended pedigrees from a Western Australian Aboriginal community. Imputation using the thousand genomes (1000G) reference panel extended the analysis to 6,724,284 post quality-control autosomal SNPs. No associations achieved genome-wide significance, commonly accepted as P<5x10(-8). Nevertheless, genes/pathways in common with other ethnicities were identified despite the arrival of Aboriginal people in Australia >45,000 years ago. The top hit (rs10868204 P (genotyped) = 1.50x10(-6); rs11140653 P(imputed_1000G) = 2.90x10(-7)) for BMI lies 5’ of NTRK2, the type 2 neurotrophic tyrosine kinase receptor for brain-derived neurotrophic factor (BDNF) that regulates energy balance downstream of melanocortin-4 receptor (MC4R). PIK3C2G (rs12816270 P(genotyped) = 8.06x10(-6); rs10841048 P(imputed_1000G) = 6.28x10(-7)) was associated with BMI, but not with T2D as reported elsewhere. BMI also associated with CNTNAP2 (rs6960319 P(genotyped) = 4.65x10(-5); rs13225016 P(imputed_1000G) = 6.57x10(-5)), previously identified as the strongest gene-by-environment interaction for BMI in African-Americans. The top hit (rs11240074 P(genotyped) = 5.59x10(-6), P(imputed_1000G) = 5.73x10(-6)) for T2D lies 5’ of BCL9 that, along with TCF7L2, promotes beta-catenin’s transcriptional activity in the WNT signaling pathway. Additional hits occurred in genes affecting pancreatic (KCNJ6, KCNA1) and/or GABA (GABRR1, KCNA1) functions. Notable associations observed for genes previously identified at genome-wide significance in other populations included MC4R (P(genotyped) = 4.49x10(-4)) for BMI and IGF2BP2 P(imputed_1000G) = 2.55x10(-6)) for T2D. Our results may provide novel functional leads in understanding disease pathogenesis in this Australian Aboriginal population.